Obstetric Violence in Childbirth Care in Baja California: Nursing Personnel Perceptions - Flores-Romero, Lizette; Viñas Velázquez, Bertha Margarita; Treviño-Siller, Sandra Guadalupe; Islas-Limón, Julieta Yadira (Frontera Norte, 2022)
This article aims to analyze nursing staff perceptions regarding the mistreatment of women during pregnancy and childbirth. A qualitative study was conducted using discourse analysis of 23 interviews with nursing staff in Baja California, Mexico. Two categories were identified: direct and indirect obstetric violence and institutional factors. The findings show that all study participants reported cases of obstetric violence against women. Factors such as the lack of medical equipment and trained professionals stand out as causes of stress that manifest as obstetric violence. Other causes are the culture of medicalization, limited knowledge of international and Mexican standards, and inadequate personnel training. In conclusion, it is essential to improve obstetric care by promoting the NOM-007-SSA2-2016 to achieve a woman-centered care model based on international recommendations. Furthermore, sufficient trained staff and medical equipment are imperative.